Terapia ocupacional social e infâncias: essa interface na produção e na visão da Rede Metuia - Brasil - Tinti, Júlia Meirelles (Universidade Federal de São Carlos, 2021)
Introduction: Academic studies on children and childhood initially focused on understanding child development and the processes that lead to adulthood, based on strongly neuropsychobiological perspectives. In recent decades, a production that seeks to apprehend children as a social actor, protagonist of their own history, has been growing, composing a set of sociocultural studies that come to designate “infancy”. In occupational therapy, however, studies with sociocultural approaches are still scarce. In terms of social occupational therapy, little is found specifically aimed at childhood, even though children are a very relevant segment when it comes to social vulnerability and poverty in Brazil, focuses of this sub-area. The main materials found in this context document interventions carried out in the early years of the Metuia Project. Objective: To identify and understand the place occupied by childhood, especially children in situations of social vulnerability, in studies and interventions carried out by the social occupational therapy branch, especially those arising from the Metuia Network in Brazil. Development: In addition to the literature review, the material collected in twelve interviews carried out with coordinators and researchers of the Metuia Centers throughout Brazil allowed an apprehension of the reasons for the relative absence of poor children in the actions of these Centers, where poor youth stand out. Discussion: Among the main reasons, there is the theoretical-practical baggage brought from the training received at the Metuia UFSCar Nucleus, where all the coordinators went and which is a pioneer in working with youth in occupational therapy in general. Likewise, it is pointed out that the emphasis given to youths stems from the fact that they occupy a non-place in front of the experiences and references brought by occupational therapy, where, on the other hand, childhoods receive greater prominence, especially in the areas of development and domains. of health; however, these do not address social issues such as cultural diversity, poverty and vulnerability, citizenship, among other issues that are mostly addressed by social occupational therapy. Thus, professionals who turn to the demands of childhood, from a social therapeutic-occupational perspective, would need to articulate more specific references. On the other hand, although the interventions carried out do not focus on children, they are and/or appear in the most common spaces of practice, territories/communities, community centers, living spaces, often becoming a contact, a link, a “gateway” for teams to access other subjects. As possible social therapeutic-occupational actions to be carried out with childhoods, collective actions, individual and institutional follow-ups were mentioned, as well as articulations in the political dimension, but which cannot refrain from giving due attention to the singularities of children in their different realities.Conclusion: Through this study, it was possible to perceive that childhoods, especially those in a situation of social vulnerability, are not totally distant from discussions of social occupational therapy and the Metuia Network, since the demands that concern them touch their productions so far; in addition, it was also identifiable that this is a topic of current interest to some researchers, although in a more individual way, adding perspectives for conducting studies and interventions.
Social occupational therapy and childhood: this interface in the production and vision of the Metuia Network - Brazil
Keywords: Infâncias; Vulnerabilidade social; Terapia ocupacional; Terapia ocupacional social; Childhood; Social vulnerability; Occupational therapy; Social occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL